Analisis Kinerja Keuangan Kabupaten/Kota Pemekaran di Sumatera Utara - Intania Melati; Putri Riani; Aina Hasibuan (MES Management Journal, 2023)
This study aims to analyze the influence of the implementation of local government autonomy on the fiscal performance of newly formed municipalities in northern Sumatra. The emphasis is on regional revenue growth after fiscal decentralization and government control over the regional economy have been implemented. According to the study findings, local economic development is positively influenced by local autonomy. However, the profit sharing is still relatively small compared to the regional budget. Several of North Sumatra's agricultural provinces, known as regencies, are not yet ready to enforce the regional autonomy laws. The majority of poor towns and cities depend heavily on the allocation funds from the General Funds and Special Distribution Funds, respectively. Keywords: regional economic decentralization, regional income distribution.